PELAKSANAAN PERATURAN BUPATI MENGENAI MEKANISME PEMUNGUTAN PAJAK SARANG BURUNG WALET DI KABUPATEN ROKAN HULU TAHUN 2017 - Priatama, Gazopi; ", Isril (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Any take and / or exploitation of the Swallow's Nest is taxed under the name of the Swallow's Nest Tax. Rokan Hulu Regent Regulation No. 35 of 2011 on Guidelines for the Implementation of Swallow Nest Tax Collection, this regulation is issued to regulate local taxes which are one of the important sources of regional income to finance the implementation of local government in performing services to the community and realizing regional self-reliance. Swallow's Nest entrepreneurs are less motivated to pay the Swallow's Nest tax, but officials of the Rokan Hulu District Revenue Agency lack socialization about the Swallow's Nest tax collection. The problems in this research are formulated as follows: How is the implementation of Bupati Regulation regarding the mechanism of tax collection of Swallow's Nest in Rokan Hulu Regency Year 2017 and what is the inhibiting factor of its implementation. The purpose of this research is to know the implementation of Bupati Regulation concerning mechanism of tax collecting of Swallow's Nest in Rokan Hulu Regency Year 2017 and its implementation inhibiting factor.In this research use descriptive research type with approach of qualitative method. This research is located in Bapenda Kabupaten Rokan Hulu. For informant research using purposive sampling technique. Data collection techniques used are observation, interview and documentation. To examine the problem the authors perform data analysis using qualitative descriptive method.The results of this study can be concluded that the implementation of the Regent Regulations on the mechanism of tax collection Swiftlet Nest in Rokan Hulu District Year 2017 has not run well. The weakness of the implementation of the mechanism of tax collection of Swallow's Nest with attention to the socialization factor of the officers and the lack of awareness from the community of Swallow's Nest owners.Keywords: Implementation, Mechanism, Tax Collection